(untitled) (Journal of Buffalo Science, 2015)
The present study was aimed to isolate and characterize phenotypically as well as genotypically bacterial strain from tracheal froth of a Murrah buffalo on the Government livestock farm (GLF) located at Hisar, Haryana. The isolate showed the cultural, morphological and biochemical properties of Mannheimia haemolytica as per Bergey’s manual of determinative bacteriology and as confirmed by GENIII microplate (biolog). However, the isolate was further confirmed as Mannheimia varigena by 16S rRNA sequencing